2012
DOI: 10.1007/s00442-011-2222-7
|View full text |Cite
|
Sign up to set email alerts
|

Resource limitation and the role of a hemiparasite on a restored prairie

Abstract: Hemiparasitic plants tend to thrive in and significantly affect plant communities in low-nutrient, high-light environments. Hemiparasites are assumed to be weak competitors for light but strong parasites, leading to the prediction that effects on hosts and communities should be a function of resource supply. We investigated the effects of light and mineral nutrients on hemiparasite-host relations in two experiments. Removal of the hemiparasite, addition of fertilizer, and full sun significantly increased total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 48 publications
4
30
0
1
Order By: Relevance
“…Although MRSW and the remnant have identical soil, Drummer silty clay loam (Soil Survey Staff Natural Resources Conservation Service, United States Department of Agriculture 2008), hemiparasite frequency is considerably lower in MRSW than WCP (30 vs. 92%), and hemiparasites have a more patchy distribution. This may allow better detection of differences along a hemiparasite abundance gradient, consistent with previous studies (Hedberg et al 2005;Borowicz & Armstrong 2012;Bao et al 2015), than in the remnant where hemiparasites are almost ubiquitous and effects may be more homogenous. That is, hemiparasites could have increased richness uniformly across the remnant, making it difficult to detect a hemiparasite effect in the absence of a frequency gradient.…”
Section: Field Studysupporting
confidence: 86%
See 3 more Smart Citations
“…Although MRSW and the remnant have identical soil, Drummer silty clay loam (Soil Survey Staff Natural Resources Conservation Service, United States Department of Agriculture 2008), hemiparasite frequency is considerably lower in MRSW than WCP (30 vs. 92%), and hemiparasites have a more patchy distribution. This may allow better detection of differences along a hemiparasite abundance gradient, consistent with previous studies (Hedberg et al 2005;Borowicz & Armstrong 2012;Bao et al 2015), than in the remnant where hemiparasites are almost ubiquitous and effects may be more homogenous. That is, hemiparasites could have increased richness uniformly across the remnant, making it difficult to detect a hemiparasite effect in the absence of a frequency gradient.…”
Section: Field Studysupporting
confidence: 86%
“…In greenhouse experiments with P. canadensis , Hedberg et al () had 25% P. canadensis mortality, and Borowicz and Armstrong () also reported high mortality. It was suggested that the greenhouse environment favored host species growth over P. canadensis growth (Hedberg et al ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Parasitism by a root hemiparasite often leads to significant biomass reduction in the host plant, which in most cases cannot be compensated by the increase in biomass of the hemiparasite (Matthies 1995;Niemelä et al 2008). Consequently, presence of root hemiparasitic plants often results in significant reduction in plant community productivity (Borowicz and Armstrong 2012;Decleer et al 2013), which is particularly the case in agricultural ecosystems where root hemiparasitic weeds occur in great abundance (Parker 2009;Rodenburg et al 2011).…”
Section: Introductionmentioning
confidence: 97%